Imaging features and differential diagnosis of multiple diaphyseal sclerosis: A case report and review of literature. Issue 33 (August 2018) - Cai, Yangting; Lin, Haixiong; Huang, Feng; Zheng, Xiaohui; Huang, Yaohua; Zhang, Shuncong
Abstract: Rationale: Multiple diaphyseal sclerosis (MDS), known as Ribbing disease, is a rare congenital bone disease resulting from autosomal recessive inheritance. The case study involved a 22-year-old female patient who had been diagnosed with chronic sclerosing osteomyelitis due to lack of knowledge about MDS. Previous studies reported rarely on this condition. Patient concerns: A 22-year-old female with MDS was analyzed. Diagnoses: MDS is characterized radiographically by a fusiform widening of the diaphyseal portion of the long bones, which is caused by a thickening of the cortex with obstruction of the medullary cavity. The pathologies are observed utilizing diagnostic imagery and are often difficult to identify. Intervention: The patient was following a suggested regimen of oral celecoxib capsules at 200 mg/day for 6 days. Outcomes: The patient's diagnosis was revised to the rare condition of Ribbing disease by reviewing the clinical history and distinctive radiography images and because the symptoms were alleviated by celecoxib capsule. We also present a review of the literature on the diagnosis and differential diagnosis of MDS based on clinical and imaging features. Lessons: MDS is rare and may often be initially misdiagnosed as another type of sclerosing bone dysplasia, thus, it is important to be aware of the existence of MDS. Once MDS is suspected, differential diagnosis should be performed to exclude other sclerosing bone dysplasias, taking into account clinical history, distinctive radiographic appearance, distribution, and laboratory and histopathologic findings. Laboratory evaluation and pathologic findings are nonspecific but assist in excluding other diagnoses. More evidence is needed to illustrate the effectiveness of medical or surgical treatments for patients with MDS.